2017
DOI: 10.1093/brain/awx074
|View full text |Cite
|
Sign up to set email alerts
|

Repurposed drugs targeting eIF2α-P-mediated translational repression prevent neurodegeneration in mice

Abstract: See Mercado and Hetz (doi:) for a scientific commentary on this article.Signalling through the PERK/eIF2α-P branch of the Unfolded Protein Response is increased in many neurodegenerative diseases. Halliday et al. identify two safe compounds – one licensed – that act on this pathway and are neuroprotective in mice with neurodegeneration. These drugs can now be repurposed in clinical trials for the treatment of dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
307
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 255 publications
(319 citation statements)
references
References 49 publications
10
307
1
1
Order By: Relevance
“…Reduction of p-eIF2α by overexpression of the phosphatase GADD34 in prion-infected mice restored levels of synaptic proteins and reversed synaptic dysfunction, preventing neuron death without changing the levels of aggregated prion protein (Moreno et al, 2012). Further work demonstrated that small molecules that inhibit PERK or that stimulate eIF2B activity also rescued pathology in this model (Halliday et al, 2015, 2017; Moreno et al, 2013). …”
Section: Neurodegenerative Diseases Associated With Dysregulation Of mentioning
confidence: 83%
See 1 more Smart Citation
“…Reduction of p-eIF2α by overexpression of the phosphatase GADD34 in prion-infected mice restored levels of synaptic proteins and reversed synaptic dysfunction, preventing neuron death without changing the levels of aggregated prion protein (Moreno et al, 2012). Further work demonstrated that small molecules that inhibit PERK or that stimulate eIF2B activity also rescued pathology in this model (Halliday et al, 2015, 2017; Moreno et al, 2013). …”
Section: Neurodegenerative Diseases Associated With Dysregulation Of mentioning
confidence: 83%
“…Additional studies in other disease models suggest that drugs that increase eIF2 activity might also be used to treat AD and tauopathy (Halliday et al, 2017; Yang et al, 2016; Zhu et al, 2013). However, while these results are potentially exciting, a careful examination of the role of eIF2α phosphorylation in ALS illustrates the importance of exercising caution in applying new treatments to patients.…”
Section: Neurodegenerative Diseases Associated With Dysregulation Of mentioning
confidence: 99%
“…These two drugs readily cross the blood-brain barrier, have little toxicity, have been previously utilized to treat depression, and are being repurposed for treating diseases such as Alzheimer disease (Halliday et al, 2017). In this study, we identified two highly promising FDA-approved drugs, trazodone and dibenzoylmethane, that are able to reduce DPR levels.…”
Section: Discussionmentioning
confidence: 99%
“…We identified that various cellular stress events converge on activation of the ISR and result in an increase in non-AUG-dependent translation of DPRs. Additionally, in mice, trazodone and 1,3 DBM prevented the disease-linked pathology and rescued memory deficits in prion-diseased and tauopathy FTD mice (Halliday et al, 2017). Therefore, we focused on examining smallmolecule inhibitors that target the ISR or translation-related pathways that are currently in use or have been used in clinical trials for neurodegenerative diseases or cancer (Bhat et al, 2015) Specifically, trazodone and dibenzoylmethane (1,3 DBM), which recover the eif2a ternary complex and prevent increased ATF4 activation in the ISR, have been shown to be non-toxic compounds that can readily cross the blood-brain barrier, unlike other p-eif2a targeting molecules such as ISRIB.…”
Section: Repetitive Neuronal Depolarization Increases C9orf72 Nre Nonmentioning
confidence: 94%
“…In particular, compounds such as GSK2606414 and ISRIB act at different levels of the PERK/eIF2α axis to inhibit the UPR and have proven effective in murine models of neurodegeneration (96)(97)(98). Nevertheless, the current studies using these modulators highlight important concerns that question the translatability of these compounds into effective treatments for human disease: the lack of long-term tolerability due to toxicity to highly secretory organs like the liver and pancreas, in particular for the PERK inhibitor GSK2606414, and the lack of solubility of ISRIB (96,97,99). Concern for systemic, long-term administration of these inhibitors also stems from the understanding that transient UPR activation is indeed beneficial to cells and has evolved as an adaptive mechanism to protect cells against instances of acute protein misfolding, only becoming pathological in chronically activated states that trigger downstream events, such as TRIB3 upregulation and TNF signaling, that can lead to cell death (60,(100)(101)(102)(103)(104).…”
Section: Discussionmentioning
confidence: 99%